Hoax bomb threats as the acts of unlawful interference that endanger aviation safety and air transportation - Ardita, I Gusti Ngurah; Ibrahim , R.; Kasih, Desak Putu Dewi (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Aviation safety is an important part of the aviation industry around the world. In international and national law in many countries, the unlawful acts that endanger the safety of aviation and air transportation are regulated in a legal instrument. One form of unlawful actions that endangers the safety of aviation and air transportation is the spread of hoax bomb threats. This prohibition is also associated with the efforts of countries to tackle terrorism. In this study, there are several interesting legal issues discussed, namely aspects of aviation safety, hoax bomb threats as a violation of law, criminal jurisdiction in a moving aircraft and legal liability of passengers committing hoax bomb threats. Aviation safety culture is the responsibility of all stakeholders. The hoax bomb threat is a false information that endangers flight safety. The applicable criminal jurisdiction is the law of the country where the aircraft is registered. These provisions apply to both the citizens of the country concerned and foreign nationals.